Participatory Sensing Systems in Privacy and Quality Preserving Multimedia Data Aggregation - Aravinda, TV; Naghabhushana; Mamatha, O (International Journal of Computer Sciences and Engineering, 2025)
with the prevalence of portable remote gadgets outfitted with different sorts of detecting capacities, another administration worldview named participatory detecting has developed to furnish clients with shiny new background. Be that as it may, the wide use of participatory detecting has its own particular difficulties, among which protection and sight and sound information quality conservations are two basic issues. Shockingly, none of the current work has completely tackled the issue of protection and quality safeguarding participatory detecting with interactive media information. In this paper, we propose SLICER, which is the primary k-unknown protection safeguarding plan for participatory detecting with mixed media information. SLICER coordinates an information coding strategy and message exchange techniques, to accomplish solid insurance of members' protection, while keeping up high information quality. In particular, we consider two sorts of information exchange systems, specifically exchange on get together (TMU) and negligible cost exchange (MCT). For MCT, we propose two diverse however complimentary calculations, including an estimate calculation and a heuristic calculation, subject to various qualities of the necessity. Moreover, we have actualized SLICER and assessed its execution utilizing freely discharged taxi follows. Our assessment results demonstrate that SLICER accomplishes high information quality, with low calculation and correspondence overhead.